English-Assisted Teaching Evaluation System Based on Artificial Intelligence and Rasch Model - Erying Guo; Li Sun (Advances in Multimedia)
In order to improve the effect of English teaching in colleges and universities, this paper analyzes the English teaching process and combines the English teaching evaluation system and the Rasch model to construct an English teaching evaluation system. Moreover, this paper analyzes the needs of English teaching evaluation and uses the mixed Rasch model in the item reflection theoretical model to study the potential classification problems of teaching. At the same time as the optimal parameter estimation, the potential optimal classification ratio is found, and it is used as the basis for the classification of English teaching grades. In addition, this paper combines the Rasch model to construct the English-assisted teaching evaluation system and analyzes the system framework and workflow. The experimental research shows that the evaluation system of college English teaching process based on the Rasch model proposed in this paper has a good effect.